Postural balance assessment in children aged 7 to 9 years, as related to body weight, height, and physical activity - Stanek Emilia; Truszczyńska Aleksandra; Drzał-Grabiec Justyna; Tarnowski Adam (Sciendo, 2015)
Study aim: the aim of this study was to determine how body height, body weight, and moderate physical activity affected postural stability in young schoolchildren.